PENERAPAN MODEL PBL TEMA 7 UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS 3 SDN GUNUNG GEDE - Fitria Suci Martind; Nita Karmila; Rahayu Kartika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT The purpose of this study is: (1) to learn the process of applying the model of the based learning problem (PBL) to enhance learning in class III.A elementary school Gunung Gede Bogor City. (2) to find an increase in the results of learning the 7 theme "technological development" of class III.A elementary school Gunung Gede Bogor City through the model for problems based learning (pbl). This study is a class action study. The data-collection technique of interviews, observations and tests. The number of subjects in this study is 34 trainees. The analysis technique in this study is quantitative and qualitative analysis. The learning process through the stage (1) orientation on problems (2) organizing learners (3) guiding investigators (4) presents results (5) analyzing and evaluating the problem. On action research this class has seen an increase in learners' pre-cycles 24%, cycles I 56%, and cycles II 85%. In addition, there has been an increase in the performance observation of teachers and learners' activities, in the I cycle the teacher's performance results in 80% and 73% learners' activities. On the II cycle the teacher's performance increased to 91% and 85% learner's activities. Keywords: Learning, Problem Based Learning (PBL), Learning Outcomes ABSTRAK Tujuan penelitian ini adalah : (1) Untuk mengetahui proses penerapan model Problem Based Learning (PBL) untuk meningkatkan pembelajaran di Kelas III.A SDN Gunung Gede Kota Bogor. (2) Untuk mengetahui peningkatan hasil belajar tema 7 “Perkembangan Teknologi” peserta didik Kelas III SDN Gunung Gede Kota Bogor melalui model Problem Based Learning (PBL). Penelitian ini merupakan penelitian tindakan kelas. Teknik pengumpulan data yaitu wawancara, observasi dan tes. Jumlah subjek dalam penelitian ini adalah 34 orang peserta didik. teknik analisis dalam penelitian ini yaitu analisis kuantitatif dan kualitatif. Proses pembelajaran melalui tahap (1) Orientasi pada masalah (2) Mengorganisir peserta didik (3) Membimbing penyidikan (4) Menyajikan hasil (5) Menganalisis dan mengevaluasi masalah. Pada penelitian tindakan kelas ini terjadi peningkatan hasil belajar peserta didik yaitu pra-siklus 24%, siklus I 56%, dan siklus II 85%. Selain itu terjadi peningkatan pada hasil observasi kinerja guru dan kegiatan peserta didik, pada siklus I hasil kinerja guru memperoleh hasil 80% dan kegiatan peserta didik 73%. Pada siklus II hasil kinerja guru meningkat menjadi 91% dan kegiatan peserta didik 85%. Kata Kunci: Pembelajaran, Problem Based Learning (PBL), Hasil Belajar